42 rules for saving your house from foreclosure a practical guide to avoiding foreclosure, navigating the loan modification process and keeping your home - Coleman, David (Super Star Press, 2009)
There is a worldwide financial crisis and you are part of it. Your home and financial future are at stake, your mortgage has adjusted to the point where you can't pay the monthly amount anymore and you are either in or close to foreclosure. The rules in this book look at how we got into this financial mess, how to deal with the bank and how to dig your way out with the best possible outcome.